2020
DOI: 10.1055/a-1273-7589
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Lactate Accumulation Rate in All-out Exercise Differs between Cycling and Running

Abstract: This study aims to compare maximal lactate accumulation rate (V̇ Lamax) and power output (Pmax) between cycling and running in terms of reliability, differences between, and correlations among modalities. Eighteen competitive triathletes performed a 15-s all-out exercise test in cycling and a 100-m sprint test in running. Each test was performed twice and separated by one week. Exercise tests in cycling were performed on an ergometer whereas sprint tests in running were performed on an indoor track. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 39 publications
6
33
1
Order By: Relevance
“…The peak SBP*HR was also higher in the treadmill group, indicating higher myocardial oxygen consumption. Moreover, even at the same exercise intensity, HR and plasma lactate concentrations were higher in the subjects performing treadmill exercise compared with those performing the bicycle ergometer exercise ( 14 , 15 ). But the multivariate regression analysis in the present study revealed that the correlation between exercise stimulation methods and events is independent of VO 2 peak.…”
Section: Discussionmentioning
confidence: 84%
“…The peak SBP*HR was also higher in the treadmill group, indicating higher myocardial oxygen consumption. Moreover, even at the same exercise intensity, HR and plasma lactate concentrations were higher in the subjects performing treadmill exercise compared with those performing the bicycle ergometer exercise ( 14 , 15 ). But the multivariate regression analysis in the present study revealed that the correlation between exercise stimulation methods and events is independent of VO 2 peak.…”
Section: Discussionmentioning
confidence: 84%
“…The participants performed the 100-m all-out sprint test and the standardised warm-up of 15 minutes including technical drills and starts as described previously 20 21 . Throughout the sprints, participants were verbally encouraged by the examiners.…”
Section: Methodsmentioning
confidence: 99%
“…ċLa max was calculated as the difference between the measured maximal post-exercise lactate concentration and resting lactate concentration (ΔLa 100 ), which was divided by the difference between t 100 and the period at the beginning of exercise for which no lactate formation is assumed (t alac ) (Eq. 1) 20 21 28 29 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides rather common procedures in exercise testing which target maximal oxygen uptake ( V°O 2max ) and/or lactate threshold ( 25 ), we developed procedures to determine maximal lactate accumulation rate ( ) as a measure of the glycolytic metabolism. These procedures demonstrated sufficient reliability, were associated to physical performance in handcycling ( 26 , 27 ) and running ( 28 , 29 ), and were modified for this case study accordingly. is derived from short sprint tests and calculated by dividing the increase in postexercise blood lactate concentration (BLC) by the assumed lactic period (in this study 3 s) ( 30 , 31 ).…”
Section: Methodsmentioning
confidence: 99%